EUFEMISME DAN DISFEMISME DALAM TALK SHOW CATATAN DEMOKRASI TV ONE - Novianti, Gita; Priyadi, Antonius Priyadi; Saman, Sisilya (Universitas Tanjungpura, 2023)
The issue with this study is how euphemisms and dysphemisms are used in Talk Show Catatan Demokrasi Tv One in terms of their types, meanings, and forms, as well as how these usages affect students learning Indonesian in high school. Analyzing the euphemisms and dysphemisms used in Talk Show Catatan Demokrasi Tv One is the goal of this study. It uses a descriptive qualitative approach. The Talk Show Catatan Demokrasi Tv One discourse, specifically the host and resource person's comments in response to the topics covered, is the source of the research data. Documentary, documentation, and note-taking procedures are all used in data collection. According to the study's findings, there are 63 different euphemisms and dysphemisms with distinct forms, types, and meanings. First, words, phrases, clauses, and sentences have been used as examples of euphemism and dysphemism. Second, these euphemisms and dysphemisms contain 8 types of euphemisms and dysphemisms including figurative expressions, one new word replacing another word, flipancy, circumlocution, hyperbole, type of re-modelling, use of borrowed terms from other languages, and use of general to specific terms. Third, the meanings of euphemisms and dysphemisms from conceptual meanings and associative meanings that refer to several references including objects or animals, body parts, diseases, events, professions, activities, and characteristics or circumstances. Fourth, this research can be an implication of learning Indonesian for class X SMA with exposition text material.